2007
DOI: 10.1182/blood.v110.11.2669.2669
|View full text |Cite
|
Sign up to set email alerts
|

A Dose Escalation Study of the Pharmacokinetics, Safety & Efficacy of Deferitrin, an Oral Iron Chelator in Beta Thalassaemia Patients.

Abstract: Iron accumulation and overload in beta thalassaemia patients are associated with significant morbidity and mortality. Iron chelators are used to manage iron accumulation but side effects and compliance issues restrict the use of available chelators. Deferitrin (Genzyme Corporation) is an orally available iron chelator intended for iron overload. Method: Patients were dosed in 4 cohorts, receiving 5, 10, 15 and 25 mg/kg/day of deferitrin. Deferitrin dosing in cohorts 1–3 was once daily for 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…However, when the ligand was given b.i.d., patients presented with elevated BUN and SCr, and the trials were discontinued. 165 The problem then became how to solve the renal toxicity problem when the chelator was administered b.i.d.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when the ligand was given b.i.d., patients presented with elevated BUN and SCr, and the trials were discontinued. 165 The problem then became how to solve the renal toxicity problem when the chelator was administered b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…The initial outcome revealed that removal of the DFT aromatic nitrogen and introduction of a hydroxyl at either the aromatic 4′ or 3′ position of DADFT ( 4 ) led to ligands with remarkably reduced toxicity in rodents and good ICE in primates. In fact, deferitrin ( 26 ) was taken into human clinical trials by Genzyme. , Initial results were very promising when the drug was given s.i.d. However, when the ligand was given b.i.d., patients presented with elevated BUN and SCr, and the trials were discontinued .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations